Profitability Analysis PT. BRI Syariah Bank Period 2009-2018 (Judging From The Effect Of Financing To Deposit Ratio And Non Performing Financing Against Return On Assets) - Syafirah Sehaq (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2019)
The world Bank states that the global economy slow down to 2,9% in 2018. Bank profitability growth in Indonesia slowed as identified through Return On Asset printed by ten large banks until Q3 2018. The aims of this research are to analyze the influence financing to deposit ratio and non performing finance into return on asset. The independent variables in this research are financing to deposit ratio and non performing finance, and the dependent variable is return on asset. The approach of this research was a descriptive quantitative. The data used are secondary data, obtained from published financial statements of BRI Syariah Bank between 2009 – 2018. The technique to analyze the data is multiple linier regression. Based on the result of the analysis showed that financing to deposit ratio variabel has negative influence into return on asset. Based on the result of the analysis showed that non performing finance variable has negative influence into return on asset.